O MORRO FOI FEITO DE SAMBA: Uma análise do samba como manifestação marginal à luz da teoria folkcomunicacional - LOPES JUNIOR, RUBENS (2018)
The purpose of this research is to classify samba as a folk-communicational manifestation. Understanding samba as a musical genre that comes from the poorer class of the population, the research adopts the theory of Folkcomunicação from Luís Beltrão (1980). For this analysis and consequent classification, it is necessary to understand the elements of samba that can be characterized as marginal and subversive in relation to the official discourse. This is why a historical panorama of Western music is presented, dealing specifically with how the musical elements that are present up to the present day in societies are constituted as inheritance of this Eurocentric logic. There is also an extensive panorama about the formation of Brazil through the three ethnic groups present: indigenous, africans and portuguese, because in a sui generis way, the miscegenation of the tupiniquim colonization is a foundation for the emergence of samba. From then on, analyzing the history of samba through a bibliographical research counterpoint between the official Eurocentric discourse and the social dynamics present in the development of Brazilian society and the elements of samba, we find that the genre is subversive, marginal and, consequently, folkcommunication